Estimating rock properties using sound level during drilling: field investigation. (21st December 2010) - Kumar, B. Rajesh; Vardhan, Harsha; Govindaraj, M.
The process of drilling, in general, always produces sound as a by-product. Sound is used as a diagnostic tool for identification of faulty components in the mechanical industry. However, its application in the mining industry for estimating rock properties has not been much explored. Knowledge of rock properties is essential for mine planning and design. An attempt has been made in this paper to estimate the rock properties using the sound levels produced during drilling. The results of this study show that sound level produced during drilling can be a promising tool for estimating rock properties.